The evolution of the Han wedding dress design research and innovation / Gu Yanping and Rose Dahlina Rusli - Yanping, Gu; Rusli, Rose Dahlina (College of Creative Arts, 2024)
China's long history has given birth to a colorful folk culture, and weddings are a significant part of life. The Chinese often use the term "married" to describe one's marital status, and wedding attire plays a crucial role in this cultural expression. Particularly in China’s dominant ethnic group, the Han, wedding dress traditions are something people pay great attention to. This article explores the evolution of Han wedding attire, detailing how it has changed since the Zhou Dynasty, up through the reforms and opening to the outside world. Throughout the dynasties, Han wedding dresses have exhibited unique characteristics and differences. With the economic, political, and cultural developments during the early Republic era, the grand and solemn traditional wedding dress gradually became westernized. However, Han Chinese traditional wedding attire remains a living cultural symbol, embodying the unique, beautiful, and mysterious essence of ancient Oriental culture, and representing the Han nationality. In designing modern Han wedding dresses, it is important to create designs that are aligned with contemporary trends while preserving the distinct characteristics of Han culture. By incorporating elements from different dynasties, such as traditional patterns, colors, fabrics, and shapes, alongside modern techniques and some western influences, innovation in Han wedding dress design can be achieved. Furthermore, through combining this research with personal innovation design practices, we can continue to inherit and carry forward the tradition of Han wedding attire, making a lasting contribution to its preservation.